PSIV-16 Impact of environmental enrichment on feedlot steer productivity and aggression - Park, Rachel M (J Anim Sci, 2019)
The objective of this study was to determine if cattle housed in a feedlot pen with a cattle brush had improved productivity and engaged in fewer aggressive behaviors compared to cattle without a brush. Pre-dominantly British and British continental crossbred steers (n = 51) were blocked by weight and assigned to one of two treatments 1) No enrichment (CON; 3 pens at 9 animals/pen; n = 26) or 2) a cattle brush (BRUSH; 3 pens at 9 animals/pen; n = 25) across a 256 day experimental period. Cattle arrived at the feedlot on d -55 relative to brush implementation and were slaughtered on d 161 and d 198 respective to weight block. Video recordings were decoded from 0800 to 1730 on d -2, -1, 0, 1, 2, 4, 8, 16, 32 and 64. Continuous observations recorded headbutting, mounting and kicking frequency. Production metrics were calculated (ADG, G:F and weekly DMI) and carcass data was collected at slaughter. A General Linearized Mixed Model (PROC MIXED) evaluated the impact of day, treatment and their interaction on behavior and the impact of treatment on productivity. Liver abscess presence was evaluated using PROC GLIMMIX in SAS. Treatment did not impact steer productivity, carcass traits or kicking frequency (P > 0.05). An interaction between day and treatment was observed for headbutting (P = 0.01) with BRUSH cattle performing fewer headbutts than CON cattle on d 1, 2, 4, 8 and 16. Treatment impacted mounting with BRUSH cattle performing fewer mounts than CON cattle (P = 0.03) and for both treatments, mounting decreased over time (P = 0.002). Cattle housed in BRUSH pens performed fewer aggressive behaviors and the presence of the brush did not negatively impact productivity. This suggests that a cattle brush could provide a lasting benefit to cattle welfare without compromising productivity.